STUDI SUHU DAN pH GELATINISASI PADA PEMBUATAN BIOPLASTIK DARI PATI KULIT SINGKONG - Dwi Pradana Putra, Dewa Made; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): SeptemberDO - 10.24843/JRMA.2019.v07.i03.p11, 2019)
The purpose of this study was to determine the effect of temperature and pH on the gelatinization process of cassava peel starch on the characteristics of bioplastics and determine the temperature and pH in the gelatinization process of cassava peel starch to produce the best characteristics of bioplastics. This research was carried out in the Faculty Food Analysis laboratory, Agricultural Technology Natural Resources (PSDA) laboratory, Production Laboratory of the Faculty of Engineering and Bioscience laboratory, Udayana University. This research was conducted from February to March 2018. The experimental design in this study was factorial Randomized Block Design (RBD) with two factors. Based on the analysis in the research conducted, getting conclusions, namely temperature and pH and their interactions have a large influence on tensile strength, elongation and elution, in the manufacture of bioplastics from cassava peel starch and samples of best cassava peel starch bioplastic found at a temperature ratio of 75? and pH5 with a tensile strength characteristic of 1.181Mpa, the breakdown extension was 13.591% and the elasticity was 8.744MPa. K ey words : temperature , pH , gelatinization , bioplastics